The Relationships between Physical and Emotional Symptoms and Health-Related Quality of Life of Patients after Percutaneous Coronary Intervention - Emil Huriani; Fitri Mailani (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Percutaneous coronary intervention (PCI) for myocardial infarction patients has been shown to provide outstanding results, yet research has shown that patient quality of life varies. However, few studies have been done on the physical and emotional symptoms that impact health-related quality of life (HRQoL) of patients who have undergone PCI.Purpose: This study aimed to identify physical (fatigue, angina, dyspnea) and emotional (stress, anxiety, depression) symptoms related to HRQoL of myocardial infarction patients after PCI.Methods: This study used a cross-sectional approach. A total of 154 patients, who were recruited using a purposive sampling method, participated in this study. The Fatigue Assessment Scale (FAS), the Seattle Angina Questionnaire-7 (SAQ-7), the Dyspnea scale (modified MRC score), the Depression, Anxiety, Stress Scale 21 (DASS-21), and the MacNew Quality of Life Questionnaire were all used to collect the data. Linear regressions were used to analyze the data.Results: The mean of the global HRQoL score was 5.11(0.90). Results on physical symptoms showed that a total of 49.4% of participants reported fatigue; the mean angina score was 69.6(12.06), and the mean score of dyspnea level was 0.63(0.92). Emotional symptoms reported that stress was at an average level (83.1%), anxiety was at a moderate level (63%), and depression was at a standard level (72.7%). The multiple linear regression analyses revealed fatigue (β=-0.22), angina (β=0.30), and anxiety (β=-0.32) as the factors related to HRQoL.Conclusion: Despite having a PCI after an acute myocardial infarction, the patients’ HRQoL was above the middle score. It was discovered that anxiety, angina, and fatigue predicted HRQOL in patients with myocardial infarction after PCI.